(untitled) (Journal of Computational Mathematics, 2019)
In this paper, a fully discrete scheme based on the L1 approximation in temporal direction for the fractional derivative of order in (0, 1) and nonconforming mixed finite element method (MFEM) in spatial direction is established. First, we prove a novel result of the consistency error estimate with order O(h^2) of EQ^rot_1 element (see Lemma 2.3). Then, by using the proved character of EQ^rot_1 element, we present the superconvergent estimates for the original variable u in the broken H^1-norm and the flux q = ∇u in the (L^2)^2-norm under a weaker regularity of the exact solution. Finally, numerical results are provided to confirm the theoretical analysis.